Electronic Library System (ELS) / Loh Wei Seng - Loh , Wei Seng (2000)
Electronic Library System (ELS) is a web based automation system which digitized manual library. Internet ploys a great role in determining the prospect of ELS. Web based system not only allow remote users to access the database of the library but also its enable the users to make use of the services provided by ELS. Therefore it is the perfect automation to convert a manual to a computerized library. The main objective of this system is basically about transforming the current manual system to the digital library. Besides upgrading and improving the overall performance of the system, this system will enable easier retrieval of information from remote location using the Internet. The functional requirements for this system ore the Acquisition module, Cataloging module, Circulation module and the OPAC system. Besides, there ore also several non-functional and general requirements. There are a lots of tools available on the market today. After considering numerous reasons, Microsoft lnterdev, Mocromedio Dream Weaver as well as Text Pad is chosen as the development tool Microsoft SQL server as the database management system (DBMS), Internet Service Manager as the server management. The methodology used to develop this system is the Model Driven Development Route which involved several systematic steps. With all the careful planning and design, this system hope to be able to turn problem to solution and most importantly it con be used as a guide in the future.